Nasopharyngeal Carcinoma and Pulmonary Lymphoepithelioma-like Carcinoma – Metastases or Synchronous Second Primary Cancer - Ming-Kai Chuang (Journal of Cancer Research and Practice, 2015)
Lymphoepithelioma-like carcinoma (LELC) of the lung is a rarely occurring disease, and only about 170 cases have been reported in the literature. Histologically, it is indistinguishable from non-keratinizing undifferentiated (Type III) nasopharyngeal carcinoma (NPC). Both cancers are associated with Epstein-Barr virus (EBV). However, clinicians should look to exclude NPC before the diagnosis of primary pulmonary LELC is made. Here, we report a 72-year-old man suffering from main pulmonary LELC with multiple small pleural nodules and type III NPC. However, unusual initial presentation raised the question whether the patient had metastatic NPC or double cancer. We reviewed the current evidence regarding the association of NPC and another EBV-related malignancy, the treatment of pulmonary LELC, and the epidemiology of NPC whose initial presentation is symptomatic lung metastasis.